KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DITINJAU DARI MINAT BELAJAR PESERTA DIDIK PADA MATERI PROGRAM LINEAR - Sinta Nauli Pasaribu; Edy Yusmin; Munaldus Munaldus (Jurnal AlphaEuclidEdu, 2023)
One of the most important mathematical skills for students to master is the ability to solve problems. Students' enthusiasm for learning is one factor that influences their ability to solve mathematical problems. This study aimed to determine how students' learning interests in linear programming material influenced their ability to solve mathematical problems. This study employs a qualitative approach with a descriptive format. Interviews, mathematical problem-solving aptitude tests, and interest-based questionnaires were the research instruments used. After that, all of the data were analyzed in three stages: data reduction, data presentation, and verification. 22 XI SMA Negeri 2 Nanga Pinoh students served as the study's participants. Nine students were chosen to be interviewed out of the 22 students. According to the findings, students in the high-interest categories were able to correctly solve problems using the stages of problem solving. Students with a moderate interest in solving problems are able to answer questions about solving problems and meet indicators, but they are still less systematic in their completion at several other stages. Students in the low-interest category can only finish when they understand the problem and have not been able to plan, implement, or reevaluate strategies